Australia's national(ist) history curriculum: history education as a site of attempted de-democratisation - Bedford, Alison; Kerby, Martin (Curriculum Perspectives, 2024)
This paper explores the contested content of the Australian history curriculum to understand the curriculum’s national(ist?) purpose and investigate if national histories can be taught in a way which combats the anti-democratic forces at play in our culture. This question will be explored through analysis of the three topics in the Australian Curriculum: History 7–10, which have a strong focus on Australian history specifically, and semi-structured interviews with secondary teachers on pedagogies for history and instilling democratic dispositions in students (UniSQ ETH2023-0315). Since Prime Minister John Howard’s call for reform of the curriculum to ensure that the national narrative “is one of heroic achievement” (Howard, 2006), the conservative right’s desire to have the curriculum deliver a singular, nationalist narrative has become increasingly more extreme. We risk an “acute crisis of democracy” (Repucci and Slipowitz, 2021, p. 1) as our students are taught a singular narrative that silences First Nations peoples and other cultural minorities. The best defence against this nascent de-democratisation of Australian history classrooms is found in the vital work of history teachers as curriculum workers. If teachers adhere to the curriculum directives focused on historical thinking skills, our students must consider “different perspectives” and use a “range of sources” (ACARA, 2023a) to make evidence-based decisions about our past. The teaching of critical thinking and the use of varied evidence which considers a range of perspectives and assesses their reliability serves as a bulwark against the monocultural assault which seeks to control the content of the curriculum. If we ensure our next generation of citizens have the skills to make informed and critical choices rather than be blind adherents to a nationalist monomyth, our pluralistic liberal democracy will not only survive but thrive.